Liver cancer cells with nuclear MET overexpression release translation regulatory protein‐enriched extracellular vesicles exhibit metastasis promoting activity. Issue 5 (8th May 2022) - Tey, Sze Keong; Wong, Samuel Wan Ki; Yeung, Cherlie Lot Sum; Li, Jason Ying Ki; Mao, Xiaowen; Chung, Clive Yik Sham; Yam, Judy Wai Ping
Abstract: MET receptor tyrosine kinase is a cell surface receptor that plays important role in embryonic development and tissue regeneration. Aberrant MET activation has been widely reported in different human cancers, making MET an attractive therapeutic target. The presence of truncated MET within the nucleus (nMET) with potential novel functions poses a great challenge to the current therapeutic strategies against MET surface receptor. Previous work has demonstrated the promoting effect of nMET in aggressive properties of hepatocellular carcinoma (HCC) cells by activating TAK1/NF‐κB signalling pathway. Herein, we report the role of nMET in modulating tumour microenvironment and tumour metastasis mediated by extracellular vesicles (EVs). EVs released by nMET overexpressing cells enhanced cell motility and provoked metastasis. Proteomic profiling revealed the enrichment of translational regulatory proteins in EVs derived from nMET overexpressing cells. These proteins include eukaryotic initiation factor (EIF), ribosomal protein small subunit (RPS) and ribosomal protein larger subunit (RPL) gene families. Knockdown of EIF3I, RPS3A and RPL10 diminished the promoting effect of EVs in cell migration invasiveness and metastasis. In conclusion, the findings reveal an unrecognized capacity of nMET to augment HCC through the release of EVs with oncogenic effect. Targeting these translation‐related proteins may serve as an alternative treatment for patients with nMET overexpression.